A survey of the pediatric radiation doses during multiphase abdominal computed tomography examinations. (November 2021) - Sulieman, A.; Adam, H.; Tamam, N.; Alkhorayef, M.; Alhailiy, A.; Alghamdi, S.; Elnour, A.; Alomair, O.; Alashban, Y.; Khandaker, M.U.; Bradley, D.A.
Abstract: This work investigates pediatric patients' radiation doses during multiphasic computed tomography (CT) abdomen procedures in six hospitals. A total of 58 (14 (24% females)) and 44 males (44, 76%) underwent CT single or multiphase procedures. A single phase and triple phase CT examination were carried a wide range of clinical indications, including renal and digestive systems pathologies. All procedures were performed at six radiology departments. Three departments are equipped with 16 slice CT machines, and the other three departments are equipped with 160, 128 and 16 slice CT machines. The overall 3rd quartile values for CTDIvol (mGy) and DLP (mGy.cm) were 8.6 ± 4.7 (mGy) and 1580 ± 594.64 (mGy.cm) per CT abdomen procedure. The current study indicates the need for dose optimization for pediatric patients by establishing proper imaging protocols based on the international guidelines. The variation in patients' doses is attributed to variation in the imaging protocols, scan length and number of phases performed per pediatric CT abdomen procedure. Highlights: Pediatric multiphasic CT abdomen procedures were performed at six radiology departments. The radiology departments are equipped with 16, 64, 128 and 160 slice CT machines. The increase in the scan length and number of phases exposed the patients to unnecessary radiation. CT dose per procedure (DLP (mGy.cm) is higher compared to previous studies Understanding of the technical factors that contribute to patient doses is essential in seeking patient's dose reduction.